Use of targeted SMS messaging to encourage COVID-19 oral antiviral uptake in South West Victoria - Naomi E Clarke; Jessica O'Keeffe; Arvind Yerramilli; Caroline Bartolo; Nomvuyo Mothobi; Michael Muleme; Bridgette J McNamara; Daniel P O'Brien; Eugene Athan; Mohammad Akhtar Hussain (Sax Institute, 2024)
Objectives: During winter 2022, as part of a multifaceted approach to optimise oral antiviral uptake in the Barwon South West region in Victoria, Australia, the Barwon South West Public Health Unit (BSWPHU) implemented an innovative, targeted SMS messaging program that encouraged people with coronavirus disease 2019 (COVID-19) to be assessed for antiviral treatment. In this study, we investigated patterns of antiviral uptake, identified barriers and facilitators to accessing antivirals, and examined the potential impact of targeted SMS messaging on oral antiviral uptake. Methods: We conducted a cross-sectional study of notified COVID-19 cases aged 50 years and older, and Aboriginal and Torres Strait Islander people aged 30-49 years, in the BSWPHU catchment area over a 6-week period commencing 21 July 2022. We analysed survey data using descriptive statistics and generalised linear models. Results: Of the 3829 survey respondents, 36.7% (95% confidence interval (CI) 35.2, 38.2) reported being prescribed oral antivirals, with 75.4% (95% CI 72.8, 77.9) of these aged ≥70. Antiviral prescriptions increased significantly over the 6-week survey period. Most prescriptions (87.5%; 95% CI 85.7, 89.2) were provided by the respondents' usual general practitioners (GPs). Barriers to receiving antivirals included respondents being unable to get a medical appointment in time (3.7%; 95% CI 3.1, 4.2), testing too late in their illness (2.3%; 95% CI 1.8, 2.8) and being unable to access medications in time after receiving a prescription (0.2%; 95% CI 0.1, 0.6). Facilitators to receiving antivirals included respondents first hearing about antivirals from a trusted source such as a family member, friend or usual doctor. Nearly one in eight people who were prescribed antivirals reported first hearing about them from the SMS message sent by BSWPHU. Conclusions: Oral antiviral treatment uptake in south-west Victoria in July−August 2022 was high among survey respondents and increased over time. GPs were the key prescribers in the community. Targeted SMS messaging to COVID-19 cases is a simple, low-cost intervention that potentially increases antiviral uptake.